2012
DOI: 10.1590/s0001-37652012000400021
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of Mitracarpus frigidus as a potent source of bioactive compounds

Abstract: In our previous work (Fabri et al. 2009), we showed that different extracts of Mitracarpus frigidus had significant antibacterial, antifungal and leishmanicidal activities. In order to increase our knowledge about this species, this work assesses the chemical composition and the in vitro biological activity of its essential oil. Thus, the essential oil obtained by hydrodistillation of the aerial parts of M. frigidus was analyzed by GC/MS. Among several compounds detected, 11 were identified, being linalool and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Mitracarpus frigidus : Chemical analysis of the M. frigidus EO obtained by hydrodistillation of the aerial parts of the plant resulted in the identification of 12 known compounds, linalool (29.29%) and eugenol acetate (15.85%) were the major constituents, followed by 5-hydroxy-isobornyl isobutyrate (8.41%), 5-methyl-1-undecene (7.69%) and methyl salicylate (6.55%) (Fabri et al ., 2012). This EO exhibited a potent antifungal effect against Cryptoccocus neoformans , Candida albicans and an expressive activity against L. amazonensis promastigote forms.…”
Section: Discussionmentioning
confidence: 99%
“…Mitracarpus frigidus : Chemical analysis of the M. frigidus EO obtained by hydrodistillation of the aerial parts of the plant resulted in the identification of 12 known compounds, linalool (29.29%) and eugenol acetate (15.85%) were the major constituents, followed by 5-hydroxy-isobornyl isobutyrate (8.41%), 5-methyl-1-undecene (7.69%) and methyl salicylate (6.55%) (Fabri et al ., 2012). This EO exhibited a potent antifungal effect against Cryptoccocus neoformans , Candida albicans and an expressive activity against L. amazonensis promastigote forms.…”
Section: Discussionmentioning
confidence: 99%
“…About 30 % of eugenol treated promastigotes and amastigotes were found to contain two or more flagella or nuclei indicating the arrest of cell division [51]. It showed anti-leishmanial activity against L. major promastigote with IC 50 value of 47.2 µg/ml [52]. Methanolic extract of Piper betle containing eugenol exhibited anti-leishmanial potential against Leishmania donovani [53].…”
Section: Anti-parasitic Activitymentioning
confidence: 99%
“…Due to this, a different sensitivity of theses parasites to the tested extracts was expected. Previous in vitro studies have also shown differences in sensitivity of Leishmania species to different reference drugs, including pentavalent antimonials, amphotericin B (Minodier and Parola 2007), miltefosine (De Morais-Teixeira et al 2011) and crude or purified plant extracts (Braga et al 2007, Fabri et al 2012a. Among the 17 methanolic extracts tested, 11 showed leishmanicidal activity against at least one promastigote forms of Leishmania species with IC 50 values ranging from 5.0 to 88.3 µg/mL.…”
Section: Resultsmentioning
confidence: 95%